Biorremediação de efluente de posto de combustível com microorganismos encapsulados - Favaretto, Danúbia Paula Cadore (2015)
The gas stations have high pollution potential. The supply, oil replace and wash of vehicles, generate effluents contaminated with oily waste oil products. The usual treatment system is a sandtrap coupled with a natural flotation tank. This treatment is not enough to remove oily contaminants due to emulsification and detergents in the wastewater. Complementary techniques can reduce the environmental damage caused by oily wastes. An alternative to physical treatments is bioremediation, which consists in using the microbial metabolism to the remove toxic constituents from the environment. Although the bioremediation can be a slow process, it has advantages as the complete mineralization of toxic compounds into simpler compounds, and does not cause the generation of toxic waste to further contamination of the environment. The aim of the work was use bioremediation as an alternative for the treatment of effluents from gas stations. Samples of effluent were collected and it was and characterized. Native microorganisms were isolated from effluent in culture in PCA (Plate Count Agar) and PDA (Dextrose Agar Plate). In a first step, microorganisms which the biosurfactants production capacity, reduction of tension surface and biomass growth and removal of oil and grease were selected potential use in bioremediation. This potential in bioremediation was confirmed by chromatographic analysis. The selected microorganisms were encapsulated in a sodium alginate gel and used for bioremediation tests. As a result, there was obtained the isolation of 14 microorganisms (fungi and bacteria), which showed good responses to the tests. Four strains of microorganisms were encapsulated in consortia and use in bioremediation of the effluent from gas station, which resulted in the removal of oil and grease (removal around 70%). Besides, the bioremediation with encapsulated microorganisms removed Chemical Oxygen Demand (the best result was approximately 78%) and Color (around 75%)